Management of Primary Obstructive Megaureter by Endoscopic High-Pressure Balloon Dilatation. IDEAL Framework Model as a New Tool for Systematic Review - Romero, Rosa M. (Frontiers in Surgery, 2019)
Introduction Therapeutic management of primary obstructive megaureter (POM) requiring surgery has been under debate for the last 15 years especially regarding the outcomes of endoscopic techniques compared to most traditional approaches. The aim of this review is to analyse endoscopic High-Pressure Balloon Dilatation (HPBD) using the IDEAL model. The IDEAL model has been developed and demonstrated its value in evaluating surgical innovations assessing data quality and providing relevant information for the optimal design and feasibility of research in surgery. Material and methods A systematic review of the published series of EHPBD in patients with POM was done using the IDEAL model as a tool to assess evidence quality. Reported clinical outcomes are also analysed and reviewed. Results The analysis of the results of the systematic assessment of the reported cohort of patients treated with HPBD for POM that the technique up to date is in stage 2a and stage 2b, or development. Evidence quality among the reported cohorts of patients with POM treated with HPBD is adequate, although systematization and standardization should be improved. Clinical outcomes of HPBD in the management of POM consistently show a success rate >87% with a negligible operative complication rate once “learning curve” has been surpassed. Symptomatic vesicoureteral reflux is the main reason for ureteric reimplantation, but asymptomatic VUR does not seem to influence clinical outcome. Conclusions The IDEAL framework and recommendations have allowed a systematic analysis of the evidence quality of the reported experience in the management of children with POM with HPBD of the vesicoureteral junction. The available evidence demonstrates that HPBD is an effective treatment for patients with POM, with a long-term success rate of 87.7% with very low morbidity. Future research mandates a standardization of data reporting, “ideally” following IDEAL recommendations, that would be required for any intervention and facilitate comparative analysis.